Effects of Congenital Blindness on Ultrasonic Vocalizations and Social Behaviors in the ZRDBA Mouse - Bouguiyoud, Nouhaila; Morales-Grahl, Elena; Bronchti, Gilles; Frasnelli, Johannes; Roullet, Florence I.; Al Aïn, Syrina (Frontiers in Behavioral Neuroscience, 2022)
Mice produce ultrasonic vocalizations (USVs) at different ages and social contexts, including maternal-pup separation, social play in juveniles, social interactions and mating in adults. The USVs recording can be used as an index of sensory detection, internal state and social motivation. While sensory deprivation may alter USVs emission and some social behaviors in deaf and anosmic rodents, little is known about the effects of visual deprivation in rodents. This longitudinal study aimed to assess acoustic communication and social behaviors using a mouse model of congenital blindness. Anophthalmic and sighted mice were assayed to a series of behavioral tests at three different ages: the maternal isolation-induced pup USV test and the home odor discrimination and preference test on postnatal day (PND) 7, the juvenile social test on PND 30-35, and the female urine-induced USVs and scent marking behavior at 2-3 months. Our results evidenced that: 1) At PND 7, USVs total number between both groups were similar, all mice vocalized less during the second isolation period than the first one, and both phenotypes showed similar discrimination and preference, favoring exploration of the home bedding odor, 2) At PND 30-35, anophthalmic mice engaged less in social behaviors in the juvenile play test than sighted ones, but the number of total USVs produced are not affected, and 3) At adulthood, when exposed to a female urine spot, anophthalmic male mice displayed faster responses in terms of USVs emission and sniffing behavior, associated with a longer time spent exploring the female urinary odor. Interestingly, acoustic behaviour in the pups and in the adults was correlated in sighted mice only. Together, our study reveals that congenital visual deprivation had no effect on the number of USVs emitted in the pups and juveniles, but affected the USVs emission in the adult male, and impacted the social behaviour in juvenile and adult mice.